Current Situation of Primary School Teachers’ Integrated STEM Teaching Competence: An Exploratory Study in the Northern Mountainous Provinces of Vietnam - Thao, N. P.; Huong, L. T. T.; Dinh, N. V.; Hang, N. T. T.; Quyen, C. V.; Cuong, L. M.; Thao, T. T. P. (Jurnal Pendidikan IPA Indonesia, 2024)
STEM educational orientation originating in the United States nearly two decades ago has been researched by many educators in many different aspects, including the requirements of teachers’ competence to teach STEM. However, STEM education has only been officially implemented on a large scale in high schools since 2019 in Vietnam. Therefore, research on STEM education and STEM teaching competence, in general, is currently a research direction of interest. This research aims to determine the current situation of integrated STEM teaching competence and participation in training for integrated STEM teaching of primary school teachers in the northern mountainous region of Vietnam. This research used a quantitative approach with an online survey of 2,416 primary school teachers in the Northern mountainous region of Vietnam, then eliminated invalid survey questionnaires and 2,305 questionnaires included in the analysis. The results of the data analysis show that teachers participate in training courses on STEM education. However, the implementation of STEM education in the Northern mountainous region of Vietnam still has many limitations, with the clear differences in affective characteristics and instructional skills between men and women; in which teachers with less than five years of experience have better integrated STEM teaching competence, which gradually decreases for older teachers; integrated STEM teaching competence also has clear differences between working areas. Based on these results, the authors propose several training and support strategies for teachers to implement STEM in teaching in the Northern mountainous region of Vietnam.